The revised UNESCO Recommendation on Technical and Vocational Education and Training is of interest to all of us! - Thomann, Birgit [Verfasser] (My University, 2017)
"In April 2016, UNESCO adopted a document which under-lines the growing global significance of vocational ed-ucation and training (VET) and represents an important milestone in terms of increasingly aligning the quality of VET to the requirements of the world of work. This article outlines the background and the process behind the development of the recommendation and defines its main contents with regard to practical relevance." (author's abstract ; BIBB-Doku)
Die überarbeitete Empfehlung der UNESCO zur Berufsbildung geht uns alle an!
Keywords: S 2.3 Berufsbildungspolitik; I 1.5 Internationale Organisationen & Institutionen; Berufsbildung; Qualitätssicherung; Internationale Zusammenarbeit; UNESCO; Empfehlung